Sleep disturbances in Norwegian children with fetal alcohol spectrum disorders (FASD) with and without a diagnosis of attention‐deficit hyperactivity disorder or epilepsy. (21st February 2023) - Gerstner, Thorsten; Sævareid, Hans Inge; Johnsen, Åse Ribe; Løhaugen, Gro; Skranes, Jon
Abstract: Background: Fetal alcohol spectrum disorder (FASD) describes a combination of developmental, cognitive, and behavioral disabilities in children with prenatal exposure to alcohol. The literature suggests that there are higher rates of sleep disturbances in these children. Few studies have investigated sleep disturbances in relation to common comorbidities of FASD. We examined the prevalence of disturbed sleep and the relationship between parent‐reported sleep problems in different FASD subgroups and comorbidities like epilepsy or attention‐deficit hyperactivity disorder (ADHD) and impact on clinical functioning. Methods: In this prospective cross‐sectional survey, caregivers of 53 children with FASD completed the Sleep Disturbance Scale for Children (SDSC). Information about comorbidities was collected, and EEG and assessment of IQ, daily‐life executive and adaptive functioning were performed. Group comparisons and ANCOVA interaction models were used to test the associations between different sleep disturbances and clinical factors that could interfere with sleep. Results: An abnormal sleep score on the SDSC was very common, affecting 79% of children ( n = 42) with equal prevalence in all FASD subgroups. Difficulty falling asleep was the most common sleep problem, followed by difficulty staying asleep and waking early. The incidence of epilepsy was 9.4%, with an abnormal EEG seen in 24.5%, and a diagnosis of ADHD in 47.2% of children. The distribution of these conditions was equal in all FASD subgroups. Children with signs of sleep disturbance had poorer working memory, executive function, and adaptive functioning. Children with ADHD had a greater prevalence of sleep disturbance than those without ADHD (OR 1.36; 95% CI 1.03 to 1.79). Conclusion: Problems with sleep are very common in FASD children and seem independent of FASD subgroup and the presence of epilepsy or a pathological EEG finding, while those with ADHD had more sleep problems. The study underscores the importance of screening for sleep disturbances in all children with FASD as these problems may be treatable. Abstract : A prospective cross‐sectional study on children with FASD with the aim to find correlations between sleep disturbance, comorbidities and neuropsychological assessments showing an overall high prevalence of disturbed sleep independent of FASD subgroup and epilepsy. Children with signs of sleep disturbance had inferior working memory, executive and adaptive functioning, while FASD with ADHD results in significant more sleeping problems. The study emphasizes the importance of screening for sleep disturbances in ALL children with FASD since these may be treatable.